2020
DOI: 10.3390/en13246740
|View full text |Cite
|
Sign up to set email alerts
|

Determining If Oil Prices Significantly Affect Renewable Energy Investment in African Countries with Energy Security Concerns

Abstract: As concerns regarding the adverse impacts of energy production and consumption on the environment grow, countries across the world are now charged with developing effective strategies that provide energy security and protect the environment. This means that efforts to generate significant investments and business opportunities to boost the growth of renewable energy need to increase rapidly. However, there are limited studies on what will facilitate the increase of renewable energy investment in Africa. The ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…The positive impact of oil prices on REI in oil-importing countries can be explained well by the fact that higher oil prices increase the cost of fossil fuels and make renewable energy more economically competitive. This finding is in accord with the findings of extant studies showing a positive relationship between oil prices and the development of renewable energy e.g., [19,32,38]. In oil-importing countries, where the cost of fossil fuels can be a significant burden on the economy, higher oil prices can make renewable energy sources more competitive, driving investments in clean energy technologies.…”
Section: Discussionsupporting
confidence: 89%
“…The positive impact of oil prices on REI in oil-importing countries can be explained well by the fact that higher oil prices increase the cost of fossil fuels and make renewable energy more economically competitive. This finding is in accord with the findings of extant studies showing a positive relationship between oil prices and the development of renewable energy e.g., [19,32,38]. In oil-importing countries, where the cost of fossil fuels can be a significant burden on the economy, higher oil prices can make renewable energy sources more competitive, driving investments in clean energy technologies.…”
Section: Discussionsupporting
confidence: 89%
“…Escalating OP should inspire families and commerce to decrease energy consumption, securing more proficient produces and shift to nonconventional power sources. (Tambari and Failler, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results suggested that oil price had a large and beneficial impact on both stock markets, albeit the effect was less obvious in South Africa. Using a VAR model to explain the link between prices of crude oil and investments in renewable energy in African states, Tambari and Failler, (2020) found that oil price shocks had a positive and statistically significant impact on African countries' investments in renewable energy. Daggash and Abraham (2017) discovered an identical phenomenon using the VAR Granger Causality Method.…”
Section: Literature Reviewmentioning
confidence: 99%